Profil zdających egzamin z języka polskiego jako obcego na poziomie C1 w jednym z ośrodków uprawnionych. Sprawozdanie z badania - Olkiewicz, Filip; Kubicka, Emilia; Dembska, Katarzyna (Neofilolog, 2026)
This article profiles candidates taking the C1-level certification exam in Polish as a foreign language, on the basis of data from questionnaires collected during seven examination sessions (2022–2025) at one of the examination centres, and candidate results. The study also explores candidate motivations. The overall pass rate was 45% and the modules on grammar, and writing were found to be the most frequently failed in each session. The paper examines correlations between failures in individual modules. Scores for each exam component were compared across different age groups to investigate potential relationships between candidates’ age and exam success.